The Effectiveness of Directed Reading Thinking Activity (DRTA) Strategy on Students' Reading Comprehension Moderated by Gender - Natasya Sugara; Hadeli Hadeli; Fitrawati Fitrawati (AT-TA'LIM, 2025)
The aim of this study was to analyse the effectiveness of the Directed Reading Thinking Activity (DRTA) strategy on the reading comprehension of eighth-grade students at SMPN 3 Luhak Nan Duo, compared to conventional strategies, and to examine the role of gender as a moderating variable. Using a quasi-experimental design with pre- and post-tests, the findings revealed that the DRTA strategy was significantly more effective than the conventional strategy in enhancing students’ reading comprehension (p 0.01). Gender also influenced performance (p 0.05), with female students tending to score higher than male students. However, no significant interaction was found between strategy and gender (p 0.05), indicating that the effectiveness of DRTA applies equally across genders. These results suggest that DRTA is an effective strategy for enhancing students' reading comprehension in junior high schools, with practical implications for teachers to adopt more interactive and gender-responsive reading instruction